The Soviet doctor and the treatment of drug addiction: "A difficult and most ungracious task" - Latypov Alisher B (BMC, 2011)
Abstract This paper reviews the development of early Soviet drug treatment approaches by focusing on the struggle for disciplinary power between leading social and mental hygienists and clinical psychiatrists as a defining moment for Soviet drug treatment speciality that became known as "narcology." From this vantage point, I engage in the examination of the rise and fall of various treatment methods and conceptualizations of addiction in Russian metropolitan centres and look at how they were imported (or not) to other Soviet republics. As clinical psychiatrists appeared as undisputed victors from the battle with social and mental hygienists, the entire narcological arsenal was subdued in order to serve the needs of mainstream psychiatry. However, what that 'mainstream' would be, was not entirely clear. When, in 1934, Aleksandr Rapoport insisted on the need for re-working narcological knowledge in line with the Marxist approach, he could only raise questions and recognise that there were almost no "dialectically illuminated scientific data" to address these questions. The maintenance treatment of opiate users, which emerged as the most effective one based on the results of a six-year study published in 1936, was definitely not attuned to the political and ideological environment of the late 1930s. Maintenance was rather considered as a temporary solution, in the absence of radical therapeutic measures to free Soviet society from "narkomania." As the Great Terror swept across the Soviet Union, Stalin's regime achieved its objective of eliminating drug addiction from the surface of public life by driving opiate users deep underground and incarcerating many of them in prisons and the Gulag camps. In the final section, I briefly discuss the changing perceptions of drug use during the World War II and outline subsequent transformations in Soviet responses to the post-war opiate addiction [Additional file <supplr sid="S1">1</supplr>]. <suppl id="S1"> Additional file 1 <text> Abstract. The Soviet doctor and the treatment of drug addiction: "A difficult and most ungracious task". A Russian translation of an abstract of this article. </text> <file name="1477-7517-8-32-S1.PDF"> Click here for file </file> </suppl>